2006
DOI: 10.1002/anie.200601302
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Crystal Beads as Supports for Biomolecular Screening

Abstract: Crystal balls: Colloidal crystal microbeads with a three‐dimensional photonic crystal structure can be fabricated with a droplet generator and their reflection spectra used as encoding elements. A multiplex bioassay demonstrates their reliability as encoded carriers (see picture: red, green, and blue beads are immobilized with human, mouse, and rabbit immunoglobulin, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 25 publications
(17 reference statements)
1
103
0
Order By: Relevance
“…22) using a co-flow PDMS chip and a tubing/pipette tip device. Similar results were reported by Gu et al later on [236]. In both cases, nano-sized seed particles in aqueous suspension droplets were emulsified in oil and the assembly was realized via the removal of water.…”
Section: Examples Of Microfluidic Particle Productionsupporting
confidence: 85%
See 1 more Smart Citation
“…22) using a co-flow PDMS chip and a tubing/pipette tip device. Similar results were reported by Gu et al later on [236]. In both cases, nano-sized seed particles in aqueous suspension droplets were emulsified in oil and the assembly was realized via the removal of water.…”
Section: Examples Of Microfluidic Particle Productionsupporting
confidence: 85%
“…These approaches are actually multistage heterophase polymerizations in which the second stage is microfluidics. The first stages, namely seed preparation, were either dispersion [234] or emulsifier-free emulsion [235][236] polymerizations. …”
Section: Examples Of Microfluidic Particle Productionmentioning
confidence: 99%
“…Zhao et al [86] demonstrated biological screening using these photonic microparticles prepared to have three diff erent colors. Red, green and blue photonic microparticles were prepared from monodisperse polymethylmethacrylate particles with diameters of 250 nm, 220 nm and 210 nm, and human, mouse and rabbit immunoglobulin G (IgG), respectively, were immobilized on the surfaces of photonic microparticles.…”
Section: Biological Toolsmentioning
confidence: 99%
“…To achieve multiplexing, it is necessary to code the beads to recognize which bead corresponds to which analyte. Various methods such as intensity of fluorescence, (12) multicolor fluorescence, (14) shape, (16) colloidal crystal, (17) metallic barcoding, (18) and surface-enhanced Raman scattering (19) have been proposed as bead-coding methods. Among these, fluorescence-based encoding is most commonly used.…”
Section: Introductionmentioning
confidence: 99%